Shari’ah corporate governance: the need for a special governance code - Hassan, Rusni; Muneeza, Aishath (Emerald Group Publishing, 2014)
With the advent of Islamic banking, a new species was added to the banking system which was then, only dominated by the conventional banking. Islamic banking expanded in the world within the last decade and as a result, Islamic finance emerged as an alternative to the conventional finance. This created Islamic companies and Islamic financial institutions which operate based on the principles of Shari’ah or Islamic Law. These Islamic corporate bodies, like the conventional corporate bodies do need good governance rules. In other words, they also need a good, sophisticated ‘‘Shari’ah Governance Code’’ which would be based on the principle of Islamic Law. This is mainly because the objective of the conventional and the Islamic Corporate governance is different as conventional corporate governance structure is more focused on the protection of the rights of the stakeholders; while Islamic corporate governance focus on retaining the Islamicity of whole corporation. The objective of this research is, as the title suggests, proposing the reasons why a special governance Code for Shari’ah corporate bodies are needed. This paper would suggest a proper governance structure to the Islamic companies and will also discuss why the conventional corporate governance Codes are unsuitable for the Islamic companies Design/methodology/approach – This research which is primarily library based, is an exploratory legal research in nature. Findings – In the course of this research, it is found that there is a need to enact a Shari’ah Corporate Governance Code due to the widespread establishment of shari’ah compliant companies in the world. Hence, the authors had discussed the potential content of such a Code in this paper. Originality/value – This research will complement the knowledge based on shari’ah corporate governance and is targeted to the existing and prospective shari’ah compliant companies. Keywords Law, Corporate governance, Islamic finance, Islamic banking, Corporate responsibility, Shari’ah governance Paper type Conceptual paper